2021
DOI: 10.1007/s00431-021-04143-7
|View full text |Cite|
|
Sign up to set email alerts
|

Hypovitaminosis D in migrant children in Switzerland: a retrospective study

Abstract: Cholecalciferol (vitamin D3) is essentially known for its role in the phosphocalcic metabolism and its associated pathologies, such as rickets. In Switzerland, 35 to 50% of children are vitamin D deficient. Due to skin colour, poor nutrition, living conditions and cultural practices, migrant population is particularly at risk. Our aim is to attest the prevalence of hypovitaminosis D in children arriving in Switzerland. We retrospectively assessed 528 children’s vitamin D status and parathyroid hormone, phospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
(54 reference statements)
0
6
1
Order By: Relevance
“…In this paper, 33.66% of rural children had a normal BMI, but 49.76% of rural children were thin, and 16.59% of rural children were overweight or obese. In terms of mental health, the average CES-D depression score of rural children is 16.82, which is less than the critical value of depression (17), indicating that most rural children had good mental health. However, 18.28% of rural children had mild depression, 11.14% had moderate depression, and 13.08% had severe depression.…”
Section: Descriptive Statistics Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…In this paper, 33.66% of rural children had a normal BMI, but 49.76% of rural children were thin, and 16.59% of rural children were overweight or obese. In terms of mental health, the average CES-D depression score of rural children is 16.82, which is less than the critical value of depression (17), indicating that most rural children had good mental health. However, 18.28% of rural children had mild depression, 11.14% had moderate depression, and 13.08% had severe depression.…”
Section: Descriptive Statistics Resultsmentioning
confidence: 88%
“…Through counterfactual analysis, some scholars have found that inequality of opportunity in nutritional outcomes in China would increase by more than 19% if rural children migrate to cities [12]. Migrant children are more likely to encounter junk food than left-behind children, and excessive calorie intake can cause overnutrition [13], obesity [14] or other diseases [15,16]. In addition, migrant parents have less time to help their children with their homework or accompany their children, which is not conducive to the mental health and cognitive ability of these migrant children [10,17].…”
Section: Introductionmentioning
confidence: 99%
“…The data clearly show that poor diet leads to nutritional deficiencies such as vitamin B12 deficiency in refugee and asylum‐seeker children. Vitamin D deficiency is due to inadequate diet, limited outdoor activities and reduced exposure to sunlight (Acoglu et al, 2020; Assi et al, 2019; Erbaş et al, 2020; Fahrni et al, 2021; Kaya et al, 2021; Klas et al, 2022; Kroening & Dawson‐Hahn, 2019; Lindsay et al, 2022; Newman et al, 2019). Our findings are consistent with previous studies (Acoglu et al, 2020; Assi et al, 2019; Erbaş et al, 2020; Fahrni et al, 2021; Kaya et al, 2021; Klas et al, 2022; Kroening & Dawson‐Hahn, 2019; Lindsay et al, 2022; Newman et al, 2019) showing chronic health problems such as anaemia, malnutrition, hypovitaminosis D, vitamin B12 deficiency, hypocalcemia, and hyperphosphatemia in refugee and asylum‐seeking children.…”
Section: Discussionmentioning
confidence: 99%
“…As some information was gathered during the COVID-19 pandemic, it is possible that changes in the participants’ dietary intake might have occurred. Several European surveys including children and adolescents reported a low vitamin D intake [ 2 , 3 ]. A study conducted in 2017 with Swiss adolescents concluded that the “vitamin D intake was below the recommendations” [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypovitaminosis D (i.e., insufficiency and deficiency of vitamin D) is common in children and adolescents with obesity [ 1 ], with prevalence rates varying between 72% (United States) and 92–96% (Germany and Russian Federation) [ 2 ]. In Switzerland, a recent study on migrant populations showed that the prevalence of hypovitaminosis D was highest in children from Eastern Mediterranean (80%) and African regions (75%) and that the prevalence of severe deficiency was highest in children from Southeast Asian (39%) and Eastern Mediterranean regions (33%) [ 3 ]. Although the mechanisms associating obesity and hypovitaminosis D are poorly understood, the main hypothesis is the sequestration of vitamin D by the adipose tissue of obese people [ 1 ], thus reducing its bioavailability [ 4 ].…”
Section: Introductionmentioning
confidence: 99%